2022
DOI: 10.1002/ijgo.14311
|View full text |Cite
|
Sign up to set email alerts
|

Menstruation: Environmental impact and need for global health equity

Abstract: SynopsisMenstrual health hygiene equity involves increasing awareness about the global environmental impact of disposable menstrual products and creating equitable opportunity for healthy hygiene products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…One narrative review 51 and one personal view 52 non‐systematically reviewed mitigation strategies regarding sustainable practices in obstetric and gynaecological surgery. One editorial explored evidence‐based mitigation strategies regarding menstrual product use 49 . One meta‐analysis 45 and one randomised controlled trial 46 reported on the effectiveness, acceptability and waste of reusable menstrual products.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One narrative review 51 and one personal view 52 non‐systematically reviewed mitigation strategies regarding sustainable practices in obstetric and gynaecological surgery. One editorial explored evidence‐based mitigation strategies regarding menstrual product use 49 . One meta‐analysis 45 and one randomised controlled trial 46 reported on the effectiveness, acceptability and waste of reusable menstrual products.…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen (77%) of the included studies referred to the environmental impact in terms of global warming 36,38–44,47,48,50–52 In total, five studies (39%) also covered other environmental impact categories such as energy consumption, ozone depletion, ecotoxicity and eutrophication 36,39,41,47,48 . Four studies (24%) reported exclusively on the weights or amount of waste generated 37,45,46,49 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Thus, to address the climate crisis requires rethinking the production, use, and disposal of the components of the healthcare chain-including menstrual products, devices/equipment related to direct patient care ranging from routine to cancer treatments-to rethinking the way hospitals themselves are run. 17 There are many solutions, but all focus on achieving a net zero emissions goal for the healthcare production lifecycle.…”
Section: Immed Iate Ac Ti On S To Addre Ss the Climate Cris Is And Th...mentioning
confidence: 99%
“…In addition to the carbon footprint related to healthcare energy use and supply chain, health care contributes directly to greenhouse gas emissions through the use of anesthetic gases and the propellants in multi‐dose inhalers, both of which can have potent greenhouse gas effects 16 . Thus, to address the climate crisis requires rethinking the production, use, and disposal of the components of the healthcare chain—including menstrual products, devices/equipment related to direct patient care ranging from routine to cancer treatments—to rethinking the way hospitals themselves are run 17 . There are many solutions, but all focus on achieving a net zero emissions goal for the healthcare production lifecycle.…”
Section: Immediate Actions To Address the Climate Crisis And The Role...mentioning
confidence: 99%